Criminal Responsibility Of Suspects And Victims Of Corruption In The Private Bribery Sector In Indonesia - Ifahda Pratama Hapsari (Universitas Muhammadiyah Gresik, 2023)
Suspects and Victims of the Arbitrariness of Authorities in the Criminal Justice System Examining whether the Criminal Enforcement Process in the case of Corruption Crimes has been carried out correctly both in the order of Making Legal Norms and in terms of Law Enforcement. Correct and fair resolution of criminal cases is not only seen from the results of the verdict handed down by the judge. Rather, it is seen from the victim who is asked to be held accountable based on the principle of business judgments and is made a suspect for the business decisions he takes in the criminal justice system.. To realize the objectives of criminal justice within the framework of the criminal justice system, the criminal justice model that is guided is actually based on the due process of law. Whether the criminal justice is enforced from the start in accordance with the provisions of procedural law (due process of law) or not (undue process), if it has been implemented in accordance with the provisions of procedural law then the justice has implemented and upheld the ideology envisioned by the rule of law (Rechtstaat). and a democratic society. In order to uphold an honest criminal justice system from start to finish as a form of ideological commitment and justice for people who are dealing with criminal trials, whether suspects, witnesses or victims, this is the main or absolute goal. The aim of this research is to determine the responsibility of a suspect and victim as a manifestation of law enforcement ideology. The method used in writing this research is normative juridical using statutory and conceptual approaches.